2021
DOI: 10.1590/1678-7757-2020-0794
|View full text |Cite
|
Sign up to set email alerts
|

Triple-blinded randomized clinical trial comparing efficacy and tooth sensitivity of in-office and at-home bleaching techniques

Abstract: Triple-blinded randomized clinical trial comparing efficacy and tooth sensitivity of in-office and at-home bleaching techniquesObjective: Our study aims to compare the efficacy and tooth sensitivity following in-office (35% hydrogen peroxide) or at-home (10% carbamide peroxide) bleaching treatments both preceded by 2% potassium nitrate (2%KF) desensitizing gel. Methodology: 130 volunteers were randomly allocated to a) in-office bleaching and a placebo at-home protocol; or b) in-office placebo and at-home bleac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 42 publications
2
9
0
2
Order By: Relevance
“…After undergoing two bleaching sessions, the b* values exhibited the most pronounced change, followed by the L* value, with the a * value trailing. This sequence corroborated the patterns observed in previous studies 42,43 . Researchers had found that alteration in b * values served as the most accurate indicator of color change 44 .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…After undergoing two bleaching sessions, the b* values exhibited the most pronounced change, followed by the L* value, with the a * value trailing. This sequence corroborated the patterns observed in previous studies 42,43 . Researchers had found that alteration in b * values served as the most accurate indicator of color change 44 .…”
Section: Discussionsupporting
confidence: 89%
“…This sequence corroborated the patterns observed in previous studies. 42,43 Researchers had found that alteration in b* values served as the most accurate indicator of color change. 44 Conversely, another study revealed that shifts in L* values were superior indicators of tooth bleaching effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This agreed with a previous study, which reported moderate and more severe sensitivity on the day the gel was applied, and it virtually decreased after 4 days for the majority of individuals. 53 Another study noted that some patients experienced "severe shock-like pain" within 1 h of treatment. In the fourth to seventh day following the procedure, the tooth sensitivity was restored to normal levels.…”
Section: Resultsmentioning
confidence: 99%